Overview of the Saudi National Mental Health Survey - Al‐Subaie, Abdullah S.; Al‐Habeeb, AbdulHameed; Altwaijri, Yasmin A. (International journal of methods in psychiatric research, 2020)
Objectives To present background information for the Saudi National Mental Health Survey (SNMHS) on the Saudi mental healthcare delivery system and previous epidemiological research on the prevalence and treatment of mental disorders in the Kingdom of Saudi Arabia (KSA). Methods Archival information and the results of a literature review are presented. Results KSA is the largest sovereign nation in the Middle East and the largest free market economy in the Middle East and North Africa. A national mental health policy has been in existence since 2006, but mental health spending still is less than in most other high‐income countries. The Ministry of Health has recently begun developing a new healthcare system based on a patient‐centered model of care that will integrate care of mental disorders with care of physical disorders. Previous epidemiological research on mental disorders in KSA has been limited, making the SNMHS important for policy planning purposes to obtain accurate estimates of prevalence, treatment, and barriers to treatment. Conclusions The SNMHS will provide valuable information for policy planning purposes on the burden of untreated mental disorders in KSA and barriers to treatment.